Songs of the Royal Zhōu and the Royal Shào Shī 詩 of the Ānhuī University Manuscripts - Meyer, Dirk (Brill, 2022)
The songs of the Royal Zhōu ("Zhōu Nán" 周南) and of the Royal Shào ("Shào Nán" 召南) have formed a conceptual unit since at least the late Spring and Autumn period (771-453 BC). With this book Meyer and Schwartz provide a first complete reading of their earliest, Warring States (453-221 BC), iteration as witnessed by the Ānhuī University manuscripts. As a thought experiment, the authors seek to establish an emic reading of these songs, which they contextualise in the larger framework of studies of the Shī (Songs) and of meaning production during the Warring States period more broadly. The analysis casts light on how the Songs were used by different groups during the Warring States period.